Analisis Isi Pesan Dakwah dalam Film Animasi Bilal: A New Breed of Hero - Sabna Sabilla; Ahmad Tamrin Sikumbang (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The animated movie Bilal: A New Breed of Hero is a modern da'wah media that tells the story of the struggle of Bilal bin Rabbah who is known for his courage in defending his faith. This study aims to analyze the da'wah message contained in the film. The method used in this research is content analysis using a qualitative approach, which involves collecting data from the dialog and actions of the characters in the film. The results showed that there were 26 scenes containing da'wah messages, divided into three categories: (1) Aqidah, 12 scenes, emphasizing the oneness of Allah, the firmness of faith, and the rejection of polytheism. (2) Shari'ah, 4 scenes, including the freeing of slaves, the building of mosques, and the call to prayer. (3) Akhlak, 10 scenes, such as compassion, courage, and forgiveness. The movie successfully conveys Islamic values creatively through storylines and strong character delivery, making it a tool for da'wah in the digital era.